Conjugated processes based on oxidation of carbon monoxide reaction. - A. S. Abdulaeva; E. A. Timashova; E. U. Bukina; I. V. Oshanina; L. G. Bruk; O. N. Temkin (Тонкие химические технологии, 2008)
The catalytic systems are proposed to oxidize CO: solutions PdX2-organic solvent, where solvent is 1,4- dioxan or tetrahydrofuran, X – Br, I. It was shown that a number of conjugated processes proceed in these systems.